2014
DOI: 10.18632/oncotarget.2343
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with the interaction between ErbB1, nucleolin and Ras as a potential treatment for glioblastoma

Abstract: The three oncogenes, ErbB receptors, Ras proteins and nucleolin may contribute to malignant transformation. Previously, we demonstrated that nucleolin could bind both Ras protein and ErbB receptors. We also showed that the crosstalk between the three proteins facilitates anchorage independent growth and tumor growth in nude mice, and that inhibition of this interaction in prostate and colon cancer cells reduces tumorigenicity. In the present study, we show that treatment with Ras and nucleolin inhibitors reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…In accord with previous reports (Farin et al., 2009), we can detect an association between EGFR and nucleolin, and this is increased in the presence of AS1411 (Supplementary Figure S10), consistent with the increased activation of EGFR under these conditions. These data are in contrast with a recent report that AS1411 inhibits the association of EGFR with nucleolin and decreases EGFR‐mediated signaling (Goldshmit et al., 2014). The inconsistencies between this recent paper and our current findings may be due to the use of different cell lines or conditions, or may add further weight to our suggestion that the activation of EGFR observed in our case may be a coincidental or secondary effect.…”
Section: Discussioncontrasting
confidence: 99%
“…In accord with previous reports (Farin et al., 2009), we can detect an association between EGFR and nucleolin, and this is increased in the presence of AS1411 (Supplementary Figure S10), consistent with the increased activation of EGFR under these conditions. These data are in contrast with a recent report that AS1411 inhibits the association of EGFR with nucleolin and decreases EGFR‐mediated signaling (Goldshmit et al., 2014). The inconsistencies between this recent paper and our current findings may be due to the use of different cell lines or conditions, or may add further weight to our suggestion that the activation of EGFR observed in our case may be a coincidental or secondary effect.…”
Section: Discussioncontrasting
confidence: 99%
“…AS1411 can be conjugated with blood-brain barrier (BBB) penetrating peptides which make it a good therapeutic agent for brain tumor [1011]. Although AS1411 induces cytotoxicity on GBM in vitro and in vivo [12], the related mechanisms remain unclear. Understanding the effect of AS1411 on glioma may solve drug resistance of GBM and promote further therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the main pharmacology of AS1411 is to interfere nucleolin (NCL), a protein that has the ability to bind to G-quadruplex-forming DNA sequences [12]. The expression of NCL is correlated with cell proliferative status and its protein level is being widely used as a bio-marker of cell proliferation; moreover, NCL expression has been shown to associate with the development and progression of various cancers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The level of NCL synthesis is correlated with the rate of cell doubling, its expression is thus greater in many tumor cells types [21,22]. NCL is a marker of several human cancer such as colorectal gastric, lung, cervical and breast carcinomas, melanoma and glioblastoma [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Ncl: a Promising Target For Cancer Therapymentioning
confidence: 99%